A broad spectrum of clinical presentations in congenital disorders of glycosylation I: a series of 26 cases. Issue 1 (1st January 2001) - de Lonlay, P; Seta, N; Barrot, S; Chabrol, B; Drouin, V; Gabriel, B M; Journel, H; Kretz, M; Laurent, J; Le Merrer, M; Leroy, A; Pedespan, D; et al.
Abstract : INTRODUCTION: Congenital disorders of glycosylation (CDG), or carbohydrate deficient glycoprotein syndromes, form a new group of multisystem disorders characterised by defective glycoprotein biosynthesis, ascribed to various biochemical mechanisms. METHODS: We report the clinical, biological, and molecular analysis of 26 CDG I patients, including 20 CDG Ia, two CDG Ib, one CDG Ic, and three CDG Ix, detected by western blotting and isoelectric focusing of serum transferrin. RESULTS: Based on the clinical features, CDG Ia could be split into two subtypes: a neurological form with psychomotor retardation, strabismus, cerebellar hypoplasia, and retinitis pigmentosa (n=11), and a multivisceral form with neurological and extraneurological manifestations including liver, cardiac, renal, or gastrointestinal involvement (n=9). Interestingly, dysmorphic features, inverted nipples, cerebellar hypoplasia, and abnormal subcutaneous fat distribution were not consistently observed in CDG Ia. By contrast, the two CDG Ib patients had severe liver disease, enteropathy, and hyperinsulinaemic hypoglycaemia but no neurological involvement. Finally, the CDG Ic patient and one of the CDG Ix patients had psychomotor retardation and seizures. The other CDG Ix patients had severe proximal tubulopathy, bilateral cataract, and white matter abnormalities (one patient), or multiorgan failure and multiple birth defects (one patient). CONCLUSIONS: Owing to the remarkable clinical variability of CDG, this novel disease probably remains largely underdiagnosed. The successful treatment of CDG Ib patients with oral mannose emphasises the paramount importance of early diagnosis of PMI deficiency.